2008
DOI: 10.1021/es800306m
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Airborne Legionella and Legionella pneumophila at a Biological Treatment Plant

Abstract: Biological treatment plants are frequently used to degrade organic substances in wastewater from wood refinement processes. Aeration ponds in such plants provide an optimal growth environment for many microorganisms, including Legionella species. To investigate whether legionellae could be dispersed as aerosols from the ponds and transported by the wind, the wetted-wall cyclone SASS 2000(PLUS) and the impactors MAS-100 and STA-204 were used to collect air samples directly above, upwind, and downwind of aeratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 33 publications
2
81
0
Order By: Relevance
“…Even though the CFU numbers (legionellae) analyzed here are much higher than that found in air near Legionella sources (e.g. 5 9 10 3 CFU/m 3 Blatny et al 2008;Mathieu et al 2006), an impact on cell viability due to the XMX-2CV sampler's physical properties would Fig. 2 The airborne particle size distribution and concentration at FFI, Kjeller (2.4 lm) (a) and Borregaard (3.5 lm) (b) expressed in log-probability plot to estimate median particle size.…”
Section: Sampling Airborne Viable Legionellacontaining Particlesmentioning
confidence: 53%
See 2 more Smart Citations
“…Even though the CFU numbers (legionellae) analyzed here are much higher than that found in air near Legionella sources (e.g. 5 9 10 3 CFU/m 3 Blatny et al 2008;Mathieu et al 2006), an impact on cell viability due to the XMX-2CV sampler's physical properties would Fig. 2 The airborne particle size distribution and concentration at FFI, Kjeller (2.4 lm) (a) and Borregaard (3.5 lm) (b) expressed in log-probability plot to estimate median particle size.…”
Section: Sampling Airborne Viable Legionellacontaining Particlesmentioning
confidence: 53%
“…Particle size information was collected from this site as Blatny et al (2008) have shown that the highest concentration of particles was directly above these ponds and that their concentration decreased downwind of the ponds. In practice, it was not convenient to measure particle size at other sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of consumer products utilizing ion-generating technology have become available to eliminate airborne pollutants, such as dust or cigarette smoke, allergens and viruses from immediate breathing spaces [5,6]. These devices work by generating a flow of negative ions that charge and bind together with airborne particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of bioaerosols is essential for controlling air quality, assessing exposure in health risk evaluation studies, identifying bioaerosol emission sources, and estimating the performance of air cleaning devices. Exposure to bioaerosols can affect human health in variety of ways including infectious diseases, acute toxic reactions, and allergies (Terzieva et al, 1996;Lee et al, 2004;Rule et al, 2007;Blatny et al, 2008). The Severe Acute Respiratory Syndrome (SARS) and the threat of avian flu are natural examples illustrating profound, daily impacts of bioaerosols on public health (Ratnesar-Shumate et al, 2008).…”
Section: Introductionmentioning
confidence: 99%